If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2 + 6i) + (8 + -5i) = 0 Remove parenthesis around (2 + 6i) 2 + 6i + (8 + -5i) = 0 Remove parenthesis around (8 + -5i) 2 + 6i + 8 + -5i = 0 Reorder the terms: 2 + 8 + 6i + -5i = 0 Combine like terms: 2 + 8 = 10 10 + 6i + -5i = 0 Combine like terms: 6i + -5i = 1i 10 + 1i = 0 Solving 10 + 1i = 0 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 1i = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 1i = 0 + -10 1i = 0 + -10 Combine like terms: 0 + -10 = -10 1i = -10 Divide each side by '1'. i = -10 Simplifying i = -10
| -4(6x+2)=-24x-8 | | 8+3n=8n+8 | | 416191*9= | | 5t-6=42-t | | m-6=m | | 2x=(7x-y)+(6-4y) | | 6-2(w+1)=6w-2(6+w) | | 7(s-4)+13= | | .47=log(x) | | 0.11x=56 | | 5-x=8-x-3 | | 4x-17=4x | | 16=4(1+7x)-8(3x-5) | | f=6/5(n-18) | | 8-3(2x+3)=11 | | 4x-5=4x+12 | | -3(2x+3)=11 | | g=5/3(p-49) | | 4-5-13-18+2= | | 14=8x+7-x | | 458000*9= | | ln(x-4)=6 | | 90=2(7x+3) | | 3x+5x-8+4-11+17x-42+7x=-6 | | -252=-7(-6x+6) | | -91=-7(3r+4) | | 8w-14=434 | | 3(-5x+2)=-84 | | 6x+27=36 | | 7x+9y=103 | | 2x^2+-2x^2= | | (5y+3)(1+y)=0 |